2021
DOI: 10.21203/rs.3.rs-650213/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Professional Variables and Staff Readiness to Utilise Internet-Based Channels for Research Communication in an Era of Covid-19

Abstract: This study assessed the professional variables of academic staff in African varsities and their readiness to Utilise Internet-Based Channels for Research Communication in an era of Covid-19. Drawing from Maslow’s hierarchy of needs theory, the study was guided by four null hypotheses. The quantitative research method based on the virtual cross-sectional survey design was adopted. A total of 8,591 academics in African universities were the targeted demographic of this study. However, data were collected from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In another development, the research of (Reisdorf et al, 2021) revealed that the major determinants of being an ICT proxy user are personal and economic variables as well as operational internet skills. Professional variables such as educational qualification, rank, experience and areas of research interest were validated by a Kruskal-Wallis test (Owan, Akah, et al, 2021) as significant factors affecting staff propensity to use electronic channels for research distribution (Owan, Akah, et al 2021). However, the current study took a different perspective to adopt a statistical approach known as Latent Class Analysis (LCA after this) to classify the characteristics of ICT users based on their use cases.…”
Section: Introductionmentioning
confidence: 99%
“…In another development, the research of (Reisdorf et al, 2021) revealed that the major determinants of being an ICT proxy user are personal and economic variables as well as operational internet skills. Professional variables such as educational qualification, rank, experience and areas of research interest were validated by a Kruskal-Wallis test (Owan, Akah, et al, 2021) as significant factors affecting staff propensity to use electronic channels for research distribution (Owan, Akah, et al 2021). However, the current study took a different perspective to adopt a statistical approach known as Latent Class Analysis (LCA after this) to classify the characteristics of ICT users based on their use cases.…”
Section: Introductionmentioning
confidence: 99%